2001
DOI: 10.1292/jvms.63.807
|View full text |Cite
|
Sign up to set email alerts
|

Activation of GABAA Receptors in the Accessory Olfactory Bulb Does Not Prevent the Formation of an Olfactory Memory in Mice.

Abstract: ABSTRACT. When female mice are mated, they form a memory to the pheromonal signal of their male partner. The neural mechanisms underlying this memory involve changes at the reciprocal dendrodendritic synapses between glutamatergic mitral cells and γ-aminobutyric acid (GABA)-ergic granule cells in the accessory olfactory bulb (AOB). Blockade of GABA A receptors in the AOB leads to the formation of an olfactory memory. In an attempt to disrupt memory formation at mating, we used local infusions of the GABA A rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Transgenic silencing and physical ablation of the vomeronasal organ established that the AOS is essential for several aspects of rodent social behavior ( Stowers et al, 2002 ; Keller et al, 2006 ). The AOB itself has also been targeted for selective manipulation in the context of social behavior ( Brennan et al, 1990 ; Otsuka et al, 2001 ; Kunkhyen et al, 2017 ). Despite the increased availability of cell type-specific transgenic tools for neuroscience, there are few tools that are selective enough to help delineate the functions of the several classes of neurons in the AOB ( Cansler et al, 2017 ; Gao et al, 2017 ; Maksimova et al, 2019 ; Zhang and Meeks, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic silencing and physical ablation of the vomeronasal organ established that the AOS is essential for several aspects of rodent social behavior ( Stowers et al, 2002 ; Keller et al, 2006 ). The AOB itself has also been targeted for selective manipulation in the context of social behavior ( Brennan et al, 1990 ; Otsuka et al, 2001 ; Kunkhyen et al, 2017 ). Despite the increased availability of cell type-specific transgenic tools for neuroscience, there are few tools that are selective enough to help delineate the functions of the several classes of neurons in the AOB ( Cansler et al, 2017 ; Gao et al, 2017 ; Maksimova et al, 2019 ; Zhang and Meeks, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic silencing and physical ablation of the VNO established that the AOS is essential for several aspects of rodent social behavior (Keller, et al, 2006; Stowers, et al, 2002). The AOB itself has also been targeted for selective manipulation in the context of social behavior (Brennan, et al, 1990; Kunkhyen, et al, 2017; Otsuka, et al, 2001). Despite the increased availability of cell type-specific transgenic tools for neuroscience, there are few tools that are selective enough to help delineate the functions of the several classes of neurons in the AOB (Cansler, et al, 2017; Gao, et al, 2017; Maksimova, et al, 2019; Zhang, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These fibers primarily terminate in the GCL, the EPL, and the MCL, where they mainly synapse on GCs (1025). The release of noradrenaline on GCs has two major effects: 1) activation of a1-adrenergic receptors induces an increase of GABA release from GCs followed by increased inhibition of MCs (1075, 1076), and 2) suppression of GCs via activation of a2-adrenergic receptors mediates disinhibition of MCs (1077,1078). A recent study has shown that different populations of accessory MCs respond differentially to noradrenaline (1079), most probably because they express both adrenergic receptor types.…”
Section: Intrinsic and Extrinsic Modulation Of Olfactory Information In The Accessory Olfactory Bulbmentioning
confidence: 99%